KEPUASAN PENGUNJUNG DESTINASI WISATA PADA 3A KOMPONEN PRODUK WISATA YOGYAKARTA - Tri Eko Yudiandri; Lestari Ningrum (Kepariwisataan: Jurnal Ilmiah, 2022)
A repeat visit to a destination is the hope and desire of all tourism business actors. Repeat visits are most likely to occur if visitors are satisfied and they have deep impressions and memories after visiting a tourist destination. By using three sub-variables of tourism product component variables (attractions, accessibility and amenities) as well as three of the five sub-variables of customer satisfaction (product quality, emotion and price), as well as descriptive, correlational and quantitative methods, this research is expected to produce data to answer the research objectives, namely wanting to know whether visitors to Yogyakarta destinations are satisfied with the components of tourism products offered and presented in Yogyakarta. Both the tourism product component variables and visitor satisfaction were assessed as quality (4.05) and satisfied (4.17), and had a strong and significant relationship (0.701).Keywords: Tourism Product Component; Visitor Satisfaction; Destination; Tourist